A review and critical analysis of global New Product Introduction and Development. (7th July 2008) - Atkinson, David; Al-Ashaab, Ahmed
This paper provides a conceptual review of New Product Introduction and Development (NPID) and includes three original contributions to the development of NPID literature. Firstly, the prior research is summarised and characterised and these categories are then used to define this literature and establish irregularities where future research might most be productively directed. The second major contribution to literature is the authors' empirical study and benchmarking of over 20 automotive suppliers in an effort to ascertain best practice. Finally this paper will discuss and evaluate the literature as it pertains to this NPID in a global context.